El juego simbólico como estrategia de enseñanza y aprendizaje en el rincón del hogar y dramatización en el nivel inicial 2, Unidad Educativa “Naciones Unidas”, cantón Pelileo, provincia de Tungurahua. - Cocha Pérez, Ana Vanessa (2023)
The current research called “Pretend play as a teaching- learning strategy at home and dramatization in early education at Naciones Unidades Educational unit in Pelileo Canton, Tungurahua Province”. The objective is to investigate the pretend play at home and dramatization in children in early education, for which a theoretical foundation was established using several bibliographical sources that were examined in order to draw conclusions that could enhance the teaching and learning process in children. This research was based on a quantitative-qualitative methodological approach because it identified the qualities of each variable, it is quantitative because in order to obtain numerical data, statistical models were used to obtain numerical data, and three types of research were also used: bibliographic research allowed us to investigate the theoretical foundations on the proposed topic, descriptive because it allowed us to clearly detail all the concepts framed in the theoretical framework, and field research because it was carried out on the scene with the initial education level 2, continuing with the analysis and discussion of results where through observation it was evidenced that both the pretend play and dramatization when implemented as a teaching and learning strategy were used as a teaching and learning strategy. Finally, activities that are beneficial for the students and that are useful for teachers and parents to contribute to the integral development of children in education within the framework of quality and warmth were carried out.